Mathematical Modeling of Wastes Pile-Up in Kwadaso Municipality in Ashanti, Ghana (European Journal of Pure and Applied Mathematics, 2020)
In this paper, a mathematical model is introduced to describe wastes pile-up in Kwadaso Municipality which categorize wastes on the streets X1(t), wastes in gutters X2(t), wastes in the dustbins X3(t), wastes in households X4(t), wastes in the market places X5(t) and the wastes sent to dumpsites X6(t). From the qualitative data, it was observed that wastes within the Municipal keeps on pilling up as time increases indefinitely. The increase is as a result of continuous enormous quantum generation of wastes which occur in the Municipality. It was also revealed that trucks were unable to carry out the expected task of carrying wastes to dumpsites regularly leading to daily overflow of wastes in Kwadaso Municipality.
Keywords: mathematical model; analytic solution; sensitivity analysis